Biodiversity monitoring of odonata in Peramun hill natural reserve, Belitung island, Indonesia: future conservation program - Pandu Ilmi Prastyanto; Thaniya Triagustine Kalimantoro; Dita Indah Sari; Fachrudin Sidik; Abentin Estim; Yasmine Anggia Sari (Journal of Hunan University, 2024)
Odonata species, including Anisoptera (dragonflies) and Zygoptera (damselflies), are well-established bioindicators of environmental quality owing to their sensitivity to water quality. This study provides a novel assessment by examining the biodiversity of Odonata across multiple habitat types—ponds, streams, and grasslands—within the Peramun Hill Natural Reserve, Belitung Island, which has not been extensively explored in previous studies. Field surveys conducted in February 2024 recorded 279 individuals, predominantly from Libellulidae and Platycnemididae families. Pond habitats demonstrated the highest species richness and diversity, with a Shannon-Wiener diversity index (H’) of 2.48 and a low dominance index (D = 0.09), indicating a stable and diverse community. Grassland areas, although less species-rich, supported adaptable species such as Pantala flavescens, whereas stream habitats, characterized by higher evenness (J = 0.95), were preferred by species sensitive to water quality, such as Prodasineura collaris. Notably, Tetrathemis flavescens, classified as Near Threatened, suggests the potential of this species to serve as a bioindicator for future biodiversity monitoring. The unique focus of this study on habitat-specific matrices highlights the importance of habitat diversity in maintaining ecological stability and species richness. Conservation efforts should prioritize collaborative management, habitat restoration, and ongoing biodiversity assessments to safeguard odonata populations and their ecosystems.